Anaerobic batch reactor treating acid mine drainage: Kinetic stability on sulfate and COD removal. (October 2019) - Martins Costa, Josiel; Piacentini Rodriguez, Renata; Sancinetti, Giselle Patrícia
Graphical abstract: Highlights: Acid mine drainage was treated using an anaerobic sequencing batch reactor. Time profiles were performed to verify COD and sulfate removal kinetics. An increase in Fe 2+ concentration decreased the sulfate and COD removal rate. The system is stable for the cycle time of 48 h. Abstract: The leaching of an acid solution containing metals and dissolved sulfate constitutes an environmental problem known as acid mine drainage (AMD). An anaerobic sequencing batch reactor designed for AMD treatment was evaluated regarding its capacity to accommodate an increase in metals concentrations. Time profiles were performed to verify chemical oxygen demand (COD) and sulfate removal kinetics. The resulting apparent kinetic constant values showed a decrease in the reaction rate at the same time that sulfate removal increased. An increase in Fe 2+ concentration from 100 to 400 mg L −1 decreased the sulfate removal rate ( K S a p ) from (0.20 ± 0.03) to (0.072 ± 0.004) h −1, and the COD removal rate ( K C O D a p ) from (0.057 ± 0.003) to (0.027 ± 0.002) h −1 . Even with the reduction in the COD and sulfate removal rates, the system was stable for the cycle time of 48 h in all operation phases.